2012
DOI: 10.1002/macp.201100530
|View full text |Cite
|
Sign up to set email alerts
|

Thorpe‐Ingold Effect on the ATRP‐Induced Cyclopolymerization of Bismethacrylate Tethered by a Substituted Silylene Moiety

Abstract: ATRP‐induced cyclopolymerization of dialkylsilylene‐tethered bismethacrylates leads to the corresponding polymethacrylate having fourteen‐membered cyclic pendants. The presence of bulky substituents on silicon is essential to facilitate the overall cyclopolymerization process in 3. Simple methacrylate derivatives do not undergo polymerization under these conditions. This observation can be understood within the framework of the Thorpe‐Ingold effect in organosilicon chemistry. The high rr stereoselectivity sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…67 The capability of generating even larger rings in the repeating units has been recently further extended. Hu et al 68 reported the cyclopolymerization using ATRP of dialkylsilylene-tethered bismethacrylates 17, generating fourteen-membered cyclic units. The polymerizations were carried out in very diluted conditions (250 μM in DMSO) using standard ATRP conditions.…”
Section: Acrylate Based-systems Providing Larger Ring Formationmentioning
confidence: 99%
“…67 The capability of generating even larger rings in the repeating units has been recently further extended. Hu et al 68 reported the cyclopolymerization using ATRP of dialkylsilylene-tethered bismethacrylates 17, generating fourteen-membered cyclic units. The polymerizations were carried out in very diluted conditions (250 μM in DMSO) using standard ATRP conditions.…”
Section: Acrylate Based-systems Providing Larger Ring Formationmentioning
confidence: 99%
“…These monomers are different from the dialkylsilylene-spaced divinyl monomers. The two vinyl groups in the latter are forced into closer proximity due to the so-called geminal Thorpe–Ingold effect . Contrary to those divinyl monomers reported in the literature for large-ring cyclopolymerization where the two vinyl groups are oriented by the conformational rigidity (e.g., chiral control and steric hindrance, etc.…”
Section: Resultsmentioning
confidence: 98%
“…In template-assisted long-range macrocyclization systems, intramolecular macrocyclization is achieved through judicious template design (Scheme B). Typical examples of these templates include 1,2-disubstituted cyclohexane, gem -disubstituted silyl ester, calixarene, and crown ether, , where the rigidity of the templates or their abilities to establish ligand–metal coordination are essential for the intramolecular ring-closing. In both rRCCP systems, a nonoptimal spacer or template between the two CC double bonds in a monomer can lead to undesired 1,2-polymerization, in which only one CC double bond participates in chain propagation, leaving unreacted dangling olefins as potential cross-linking sites detrimental to polymerization control.…”
Section: Radical Cascade Polymerizationmentioning
confidence: 99%
“…In both rRCCP systems, a nonoptimal spacer or template between the two CC double bonds in a monomer can lead to undesired 1,2-polymerization, in which only one CC double bond participates in chain propagation, leaving unreacted dangling olefins as potential cross-linking sites detrimental to polymerization control. It is also noteworthy that rRCCP can greatly benefit from the recent developments of controlled radical polymerization techniques, including atom transfer radical polymerization (ATRP), ,, reversible addition–fragmentation chain-transfer polymerization (RAFT), ,, and nitroxide-mediated polymerization (NMP) . These developments allow for precise control over polymerization rate, dispersity, architecture, and sequence.…”
Section: Radical Cascade Polymerizationmentioning
confidence: 99%